2013
DOI: 10.2298/mpns1302011r
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators of mass and distribution of adipose tissue in the assessment of cardiovascular and diabetes risk in women

Abstract: The waist-to-stature ratio is the best anthropometric indicator of cardiovascular and diabetes risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[4] Based on a study of 155 middle-aged women mean, it was found that WHtR has been shown to correlate best with the risk of developing cardiovascular disease (score-systems: Framingham and Prospective Cardiovascular Munster Study) and the risk of developing type II diabetes mellitus (QDScore system. [20] Predictive value of anthropometric indicators was compared. Studies of 2339 children and adolescents aged 8–18 years using DXA and anthropometric methods have shown that the WHtR identifies VAT accumulation better than BMI and WC together.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Based on a study of 155 middle-aged women mean, it was found that WHtR has been shown to correlate best with the risk of developing cardiovascular disease (score-systems: Framingham and Prospective Cardiovascular Munster Study) and the risk of developing type II diabetes mellitus (QDScore system. [20] Predictive value of anthropometric indicators was compared. Studies of 2339 children and adolescents aged 8–18 years using DXA and anthropometric methods have shown that the WHtR identifies VAT accumulation better than BMI and WC together.…”
Section: Discussionmentioning
confidence: 99%